Suitability Analysis of the Potential Gas Fields of Bangladesh for Carbon Dioxide Sequestration and A Simulation Approach for Titas Gas Field - Hoque, S. M. S.; Iqbal, M. A.; Ahmed, S. I.; Islam, M. A. (Journal of Scientific Research, 2019)
Global warming has become one of the major environmental issues all over the world. The temperature of the world is increasing day by day, and fortunately, everybody wants to mitigate this fearful condition from own perspective. Carbon dioxide sequestration is a worldwide recognized project for making huge amount of carbon inactive, which is the main component of greenhouse gases, by sequestrating it beneath the Earth. The paper aims to dictate the probable success of CO₂ sequestration in Bangladesh. As abandoned gas fields are the best options for sequestration, characteristics of the potential gas fields of Bangladesh have been analyzed according to Stefan Bachu's method of classification for CO₂ sequestration. Titas gas field shows the best suitability, and accordingly, an Eclipse simulation software basis approach has been taken for this field to determine possible outcomes from probable sequestration project. Simulation result predicts an amount of 2.92 Tcf carbon dioxide gas to be sequestrated after 50 years of simulation. Other criteria such as field pressure, gas saturation are also evaluated.